ENGLISH LECTURER’S UNDERSTANDING TOWARDS WORLD ENGLISHES - Sinaga, Dwi Bora Kurniawati; Melvina, Melvina; Suharni, Suharni (TELL - US JOURNAL, 2025)
This qualitative research design is meant to explore English lecturers’ understanding which the opinion toward World Englishes and also to get to know about how their opinion about the idea of incorporating World Englishes in the English Language Teaching. The researcher uses semi-structured interview to seven English lecturers who active teaching in a class from a private university in West Sumatera. The data collected are analyzed by the thematic analysis technique. The result of this research shows that all the informants acknowledged the existence of World Englishes and also embraced the diversity of English they faced. The concept of World Englsihes which mostly explained by the informant is about the diversity that created by the cultural background and the place where the speakers come from, particularly in their accent. Moreover, for the English lecturer’s opinion about the idea of incorporating World Englishes in the classroom was still remains doubtful and challenging.